The Placement of Obsessive-Compulsive Symptoms Within a Five-Factor Model of Maladaptive Personality. (April 2023) - Cooper, Samuel E.; Hunt, Christopher; Stasik-O'Brien, Sara M.; Berg, Hannah; Lissek, Shmuel; Watson, David; Krueger, Robert F.
Dimensional models of obsessive-compulsive (OC) symptoms, as seen in obsessive-compulsive disorder (OCD), are instrumental in explaining the heterogeneity observed in this condition and for informing cutting-edge assessments. Prior structural work in this area finds that OC symptoms cross-load under both Negative Affectivity and Psychoticism traits within the Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5 ) Alternative Model of Personality Disorder (AMPD). However, tests of OC symptoms in conjunction with assessments of the full AMPD structure and its 25 lower-level facets representing narrower symptom content are lacking. We applied joint exploratory factor analysis to an AMPD measure (Personality Inventory for DSM-5 ; PID-5) and OC symptom data from two separate samples (total N = 1, 506) to locate OC symptoms within AMPD space. OC symptoms cross-loaded on Negative Affectivity, Psychoticism, and on the low end of Disinhibition. We also report exploratory analyses of OC symptom subscales with PID-5 variables. Results are discussed in the context OC symptoms' location in PID-5 space, implications for assessment, and placement of OCD within the Hierarchical Taxonomy of Psychopathology.